Risk Factors for Adverse Outcome in Pregnant Women with Obstructed Labor - Thapa, Baburam Dixit; Regmi, Mohan Chandra; Rai, R (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: The aim of the study was to assess the risk factors for adverse outcomes in pregnancy with obstructed labor. Methods: It was a prospective descriptive study conducted at BP Koirala Institute of Health sciences (BPKIHS).The patients with obstructed labour were managed and followed up until delivery and six weeks postpartum from Jan to Dec 2012. Results: There were 57 (0.6%) cases of obstructed labour out of 9500 deliveries. The main cause was cephalopelvic disproportion in 36 (63.2%). The majority of the cases were from rural areas, low socioeconomic status, non salaried and illiterate. Risk for maternal mortality, peripartum hysterectomy and perinatal mortality as adverse outcomes was significantly associated with low socioeconomic status (AOR 12.5, P=0.02) and literacy status (AOR 21.9, P=0.001). If only the risk of perinatal mortality is taken as an adverse outcome, it is significantly associated with booking status (AOR 7, P=0.001), low socioeconomic status (AOR 9.62, P=0.037) and literacy of the patient (AOR 15, P=0.001). Perinatal mortality rate was 100 per 1000 live births in women with obstructed labour. The case fatality rate was 1.2%.